A causal model of spiritual leadership and self-development: A case study of the Naqshabandiyah Khalidiyah spiritual order in Malaysia / Mohamed Safiullah Munsoor - Mohamed Safiullah , Munsoor (2018)
The contemporary period signifies a turbulent time, where internal and external strife is on the rise, increasing the burden on human beings. It is in this kind of situation that one tends to search inwardly, while concurrently pursuing external solutions. In order to find a sense of peace and meaning of life, most traditions, including Hindu, Buddhist and the Christian monastic traditions, have emphasized the inward aspects, which is largely exemplified through contemplative practices combined with related moral codes. Islam, with its transition through contemporary times, has been seen to place more emphasis on externalities, while loosing the spirit of the inwards dimension and practices known as ï¿½tasawwufï¿½; the hallmark of the Prophetic life. There is increasing evidence of these spiritual practices having a positive impact on well-being, as corroborated by emerging neuro-science data. This study poses the fundamental question: is there an architecture of the development of the self within Islam? The study goes on to explore this using an in-depth case study of the life of a Spiritual Order in Malaysia. While developing the narrative within the Islamic tradition, data from neuro-science and humanistic psychology has been used to augment the research findings. The Interpretive Phenomenology Approach (IPA) was utilised, which enabled the gaining of insight into the personal and spiritual world of the leader and the seekers. The inter-linked methods within IPA were used, including thematic analysis and Neuro-Semantics-Neuro-Linguistic Programming. The emerging data set was constructed through the use of the ï¿½clean languageï¿½ approach, which builds on the original narratives of the subjects, with methodological triangulation including interview and survey data. The synthesis, which resulted from this process, was a fusion of diverse areas of knowledge. There were four fundamental findings, which substantiates the claim that ï¿½Islam has a spiritual architecture, with its approaches, methods and tools that can be utilized for modeling and developing oneselfï¿½. Firstly, from the data set, a causal model of Spiritual Leadership and Self-Development was conceptualised, where the following essential variables were identified and explained: i) within the context of the Self, the ï¿½calling (self-realization)ï¿½ followed by the ï¿½effortsï¿½ of the seekers; and ii) within the framework of the Spiritual Order, the ï¿½Leaderï¿½s valuesï¿½ and ï¿½behaviorï¿½, as well as the ï¿½membershipï¿½ of the seekers, which provided the required guidance and knowledge. All of these influenced the ï¿½performanceï¿½ and ï¿½rewardsï¿½ impacting on the seekers ï¿½well-beingï¿½ and their ï¿½acquisition of knowledgeï¿½. This model needs to be tested to be further validated and to make it more robust. Secondly, the nexus between worship and morality exemplified by the modeling of the spiritual leadership, as well as the adaption of the various practices, is seen to lead the seeker to a more holistic development of the seeker, represented by a fusion of both the inward and the outward aspects of Islamic practices. Thirdly, the integration of the heart-brain as experienced by the seekers is seen as being critical factor for self-development. This signifies the integration of both contemplative methods attuned to the heart, combined with the more cognitive aspects of learning and practice represented by the brain. Finally, a spiritual theory of learning is postulated, which includes: observation-attention, reflection, self-accounting, supplication, mirroring, testing and retention, reproduction, internalization, and motivation. It is expected that there will be future studies to validate the causal model of spiritual leadership, self-development, and the spiritual theory of learning.